Herramientas de marketing digital para el posicionamiento de la marca “Pastora Sol” - Barre Zambrano, Carlos Steven (2024)
The general objective of the research was to determine the digital marketing tools for the positioning of the “Pastora Sol” brand in the Tosagua canton. The company was characterized, identifying the digital tools used in social networks, and the scope and segment of the target audience was analyzed, which is mainly composed of consumers between 25 and 45 years old, interested in artisanal and healthy products. The methodology used included an interview with the company manager, which provided valuable information about the strengths, weaknesses, opportunities and threats that "Pastora Sol" faces in the digital environment. The results revealed that, although the brand has a solid history of more than 45 years, its visibility on social networks is limited and depends largely on customer recommendations. It was concluded that a well-structured social media proposal could increase knowledge about the benefits of their organic and artisanal chocolates. Additionally, opportunities were identified to educate consumers and improve customer satisfaction through informative content and social media promotions. The implementation of appropriate digital marketing tools will allow "Pastora Sol" to strengthen its market positioning and attract a broader audience, taking advantage of the growing demand for local and organic products.